Bond Strength of Metal and Ceramic Brackets on Resin Nanoceramic Material With Different Surface Treatments - Mehmet Kara; Özgür Demir; Mehmet Doğru (Turkish Journal of Orthodontics, 2020)

(untitled)
Objective:This study aimed to evaluate the effects of different surface conditoning methods on surface texture and shear bond strength (SBS) of brackets bonded to resin nanoceramic material.Methods:Ceramic specimens were divided into two groups as metal brackets and ceramic brackets. In each group, the following five subgroups were conditoned with orthophosphoric acid (OPA), hydrofluoric acid (HFA), silica coating with Cojet, Nd: Yag laser, and Femtosecond (Fs) laser. Extra samples were used for scanning electron microscopy and 3D profilometer evaluation.Results:All surface conditioning methods caused optimum or higher SBS. Metal brackets had higher SBS than porcelain brackets, but this difference reached statistical significance only in Fs laser group. OPA caused surface modification comparable to HFA because of polymer content of resin nanoceramic. Although Fs laser and Cojet conditioning caused optimum or higher SBS, surface damage of these methods to the resin nanoceramic specimens clearly seen on 3D profilometer.Conclusion:HFA and Nd: Yag laser are effective surface conditioning methods for resin nanoceramics. OPA combined with silane application caused optimum SBS and can be used as an alternative to HFA. Surface texture changes should be considered to determine surface damage while deciding the optimum surface conditioning method for ceramics other than SBS.